O efeito jurídico do ato médico na interrupção da gravidez: a vida como dano - Borges, Gabriel Oliveira de Aguiar (2019)
From a literature review, this study seeks to understand the right of living and the concept of damage in civil liability in order to find the application of a “right not to be born” in Brazilian Law. Understanding the possibilities of damage and the details regarding the right of living, the life damage will be explained in such a way it makes possible to analyze the doctor’s liability for not informing the mother about the fetus handicaps, making it impossible to exercise the right to get an abortion and, therefore, avoid an impossible life.